Targeted deletion of a 170 kb cluster of LINE1 repeats: implications for regional control - Soares, Miguel Luz; Edwards, Carol A; Dearden, Fran L; Ferron, Sacramento Rodriguez; Curran, Scott; Corish, Jenny; Rancourt, Rebecca; Allen, Sarah; Charalambous, Marika; Ferguson-Smith, Malcolm A; Rens, Willem; Adams, David; et al. (Genome Research, 2018)
Around half of the mammalian genome is composed of repetitive sequences and accumulating evidence suggests that some may have an impact on genome function. Here, we characterised a large array class of repeats of long-interspersed elements (LINE-1). Though widely distributed in mammals, locations of such arrays are species-specific. Using targeted deletion, we asked whether a 170 kb LINE-1 array located at a mouse imprinted domain, might function as a modulator of local transcriptional control. The LINE-1 array is lamina-associated in differentiated ES cells consistent with its AT-richness, and although imprinting occurs both proximally and distally to the array, active LINE-1 transcripts within the tract are biallelically expressed. Upon deletion of the array, no perturbation of imprinting was observed and abnormal phenotypes were not detected in maternal or paternal heterozygous or homozygous mutant mice. The array does not shield non-imprinted genes in the vicinity from local imprinting control. Reduced neural expression of protein-coding genes observed upon paternal transmission of the deletion is likely due to the removal of a brain-specific enhancer embedded within the LINE array. Our findings suggest that presence of a 170 kb LINE1 array reflects the tolerance of the site for repeat insertion rather than an important genomic function in normal development.
10.1101/gr.221366.117